Kinetic proofreading in T-cell receptor signal transduction. - McKeithan, T W (1995)
Like other cell-surface receptors with intrinsic or associated protein-tyrosine kinase activity, the T-cell receptor complex undergoes a number of modifications, including tyrosine phosphorylation steps, after ligand binding but before transmitting a signal. The requirement for these modifications introduces a temporal lag between ligand binding and receptor signaling. A model for the T-cell receptor is proposed in which this feature greatly enhances the receptor's ability to discriminate between a foreign antigen and self-antigens with only moderately lower affinity. The proposed scheme is a form of kinetic proofreading, known to be essential for the fidelity of protein and DNA synthesis. A variant of this scheme is also described in which a requirement for formation of large aggregates may lead to a further enhancement of the specificity of T-cell activation. Through these mechanisms, ligands of different affinity potentially may elicit qualitatively different signals.